Investigating Care Dependency and Its Relation to Outcome (ICARE): Results From a Naturalistic Study of an Intensive Day Treatment Program for Depression - Glanert, Sarah; Sürig, Svenja; Grave, Ulrike; Fassbinder, Eva; Schwab, Sebastian; Borgwardt, Stefan; Klein, Jan Philipp (Frontiers in Psychiatry, 2021)
This study explores the association of experienced dependency in psychotherapy as measured with the CDQ (Care Dependency Questionnaire) and treatment outcome in depression. Further more, the course of care dependency and differences in the CDQ scores depending on the received type of treatment, MCT (Metacognitive Therapy) or CBASP (Cognitive Behavioral Analysis System of Psychotherapy), were investigated. The study follows a prospective, parallel group observational design. Patients suffering from depression received an eight weeks intensive day clinic program, which was either CBASP or MCT. The treatment decision was made by clinicians based on the presented symptomatology and with regard to the patients’ preferences. The patients reported depressive symptoms with the QIDS-SR16 (Quick Inventory of Depressive Symptomatology) and levels of experienced care dependency with the German version of the CDQ on a weekly basis. 100 patients were included in the analyses. Results show single aspects of care dependency as possible significant, negative predictors for change scores of depressive symptomatology in two out of four analyses. Levels of care dependency as well as depressive symptoms decreased significantly over the course of treatment. There was no significant between-group difference in care dependency between the two treatment groups. The results suggest that care dependency might be associated with a worse treatment outcome in depressed patients. In general, care dependency seems to be a dynamic construct, as it is changing over time, while the levels of care dependency seem to be independent from the received type of treatment. Future research should continue investigating the mechanisms of care dependency in a randomized controlled design.